Totally Minimally Invasive Esophagectomy and Gastric Pull-Up Reconstruction with an Intrathoracic Circular Stapled Anastomosis with a Team of Two (Surgeon and Assistant Only) - Grimminger, Peter P.; Lang, Hauke (The Thoracic and Cardiovascular Surgeon, 2018)
Totally minimally invasive esophagectomy (MIE) is nowadays en vogue.12345 There are several reports showing that already partial minimally invasive esophagectomies (hybrid esophagectomies) with a laparoscopic approach and open transthoracic resection are beneficial for patients due to the reduced operative trauma. Also for total MIE several groups have reported benefits for patients in terms of morbidity and quality of life.15 However, different approaches and experiences of different esophageal surgery groups are hardly comparable and thus do not allow a simple answer in favor of a specific total MIE technique. To enlighten the field of total MIE, we present the technique as we perform this procedure nearly weekly in our department. The described MIE technique is safe and feasible. Changing to this demonstrating technique, we did not have any mortality so far, even in the first 30 cases. Especially for surgeons who plan to switch from the open surgical technique toward hybrid, MIE or robotic-assisted MIE.
Keywords: MIE; MI ILE; Ivor Lewis; minimally invasive esophagectomy; thoracoscopic esophagectomy